Răspuns :
Răspuns:
Explicație pas cu pas:
a = 11
b + c = 8
ab + ac = a*(b + c) = 11*8 = 88
2a + 3b + 3c = 2a + 3*(b + c) = 2*11 + 3*8 = 22 + 24 = 46
ab + ac - 34 = a*(b + c) - 34 = 11*8 - 34 = 88 - 34 = 54
ab + ac + 25 = a*(b + c) + 25 = 11*8 + 25 = 88 + 25 = 113
10a + 9b + 9c = 10a + 9*(b + c) = 10*11 + 9*8 = 110 + 72 = 182
7b + 7c + 9a iti ramane de rezolvat
Răspuns:
a) axb+axc=11b+11c=11(b+c)=11x8=88
b.2x11+3(b+c)=22+3x8=22+24=46
c) 10x11+9(b+c)=110+9x8=110+72=182
d.a(b+c)+25=11x8+25=88+25=113
e.a(b+c)-34=11x8-34=88-34=54
f) 7(b+c)+9x11=7x8+99=56+99=155